Activities of the Dome Fuji Station wintering party of the 44th Japanese Antarctic Research Expedition in 2003-2004 - Ichio Obinata (National Institute of Polar Research, 2005)
The 44th Dome Fuji Wintering party, consisting of eight personnel, carried out observation and logistic works at Dome Fuji Station (77°19S, 39°42E, 3810m a.s.l.) from 19 January 2003 to 23 January 2004. It was the 4th wintering after the 36th, 37th and 38th Japanese Antarctic Research Expedition (JARE) parties during Deep Ice Coring Project I. Meteorological, glaciological and human physiological research were done as same as the past wintering, and observations of upper atmosphere physics were carried out for the first time. Many valuable results were achieved in each field of research. Our most important duty during wintering was to complete construction of a new ice coring site during wintering for Deep Ice Coring Project II and to start drilling with five members of the 45th summer drilling team which arrived at the inland station by airplane without using a ship from Japan for the first time in the history of JARE. There was neither a major injury nor accident during wintering. We safely completed construction of the new drilling site according to schedule and we conducted the first season's deep ice core drilling of the Project II to a depth of 362m at last.